Explaining the demand and supply model with the cost-benefit rule. (November 2020) - Sepulveda, Cristian F.
Abstract: This paper provides a simple and intuitive explanation of the demand and supply model based on the cost-benefit rule. This rule states that an action (e.g. to buy or to sell) should be undertaken only if its benefits are greater than its costs. The approach is not novel, but standard introductory textbooks only use it to explain few isolated aspects of the demand and supply model. In this paper the demand and the supply are both fully derived by simply sorting and counting the transactions that pass the cost-benefit rule for buyers and sellers. The emphasis on this rule has two main advantages. First, it makes the model more relatable, as it is more easily applied to everyday concepts and decisions students are familiar with. Second, it provides new students of economics with a clear explanation of how, in general, the discipline of economics approaches the analysis of decisions and behavior.